Static and dynamic behavior of hemp natural fiber felt biocomposites - YAYLA, PAŞA (My University, 2023)
© 2023 The Author(s). Published with license by Taylor & Francis Group, LLC.Biocomposites are a strong alternative to synthetic fiber-reinforced composites due to their environmentally friendly nature, ease of availability, cost-effectiveness, and non-toxicity. Felt biocomposites are generally favored for their better sound and temperature absorption capabilities rather than load-bearing materials due to their comparatively weak mechanical properties. However, their mechanical performance is greatly improved when they are fabricated as plates using traditional techniques like compression molding. This study focuses on the mechanical characterization and comparison of different types of hot-pressed felt biocomposite plates with a 50% by weight natural fiber content. Four unique biocomposite felts were produced and subjected to tensile, compressive, shear, instrumented Charpy v-notched impact, and drop weight impact tests. All felt kinds are reinforced with short hemp fibers and four distinct polymers are used as matrix materials, namely, polypropylene, recycled polypropylene, polylactic acid, and low-melt polyester fiber. Static and impact tests performed on those materials revealed that each type of natural fiber felt biocomposite has its unique features, and their characterized static and impact behaviors vary significantly from one to another. Therefore, each can be an appropriate material choice in an engineering design.

生物复合材料是合成纤维增强复合材料的有力替代品, 因为其环保性、易 获得性、成本效益和无毒性. 毛毡生物复合材料由于其相对较弱的机械性 能, 通常因其更好的声音和温度吸收能力而非承重材料而受到青睐. 然而, 当它们使用传统技术（如压缩成型）制成板材时, 它们的机械性能会大大 提高. 本研究侧重于具有50重量%天然纤维含量的不同类型热压毡生物复 合材料板的机械特性和比较. 生产了四种独特的生物复合毡, 并进行了拉 伸、压缩、剪切、仪表化夏比v形缺口冲击和落锤冲击试验.所有类型的毛 毡都用短大麻纤维增强, 四种不同的聚合物用作基质材料, 即聚丙烯、再生 聚丙烯、聚乳酸和低熔点聚酯纤维. 对这些材料进行的静态和冲击试验表 明, 每种类型的天然纤维毡生物复合材料都有其独特的特征, 它们的特征静 态和冲击行为各不相同. 因此, 在工程设计中, 每种材料都可以是适当的材 料选择
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, BİYOMATERYAL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, BIOMATERIALS; Malzeme Bilimi (çeşitli); Fizik Bilimleri; Materials Science (miscellaneous); Physical Sciences; biocomposites; Felt; hemp fiber; mechanical properties; natural fiber; static and dynamic behavior; 感觉; 大麻纤维; 生物复合 材料; 静态和动态行为; 机 械性能; 天然纤维